PARAMETER GENETIK DAN KORELASI GENOTIPIK KARAKTER BATANG DENGAN TOLERANSI KEREBAHAN 26 GENOTIP SORGUM (Sorghum bicolor (L.) Moench) - Anas Anas; Meddy Rachmadi; Setiawan Setiawan; Mansyur Mansyur (Indonesian Journal of Applied Sciences, 2015)
AbstractInformation of genetic variability and heritability of sorghum stem are very important for lodging-tolerant breeding program. Genotypic correlation of stem morphological character to lodging tolerance is very useful in selection program. The objectives of this experiment were to observe variability and heritability of stem character and to determine stem character that correlate with lodging tolerance. Field experiment was carried out in experimental station of Agriculture Faculty Universitas Padjadjaran. The results showed that all stem characters showed wide genetic variability except stem density and stem diameter. Low and medium heritability were showed also by stem density and stem diameter. Other stem characters showed high estimation of heritability value. Stem elasticity and number of inter-node showed negative correlation to oblique angles of stem. Other stem characters had no correlation with lodging tolerance.Keywords: genotypic correlation, heritability, lodging, sorghum, variability